Coordination mechanisms for COVID-19 in the WHO Regional office for Africa - Nsenga Ngoy; Boniface Oyugi; Paul O. Ouma; Ishata Nannie Conteh; Solomon Fisseha Woldetsadik; Miriam Nanyunja; Joseph Chukwudi Okeibunor; Zabulon Yoti; Abdou Salam Gueye (BMC, 2022)
Abstract Aim This study describes the coordination mechanisms that have been used for management of the COVID 19 pandemic in the WHO AFRO region; relate the patterns of the disease (length of time between onset of coordination and first case; length of the wave of the disease and peak attack rate) to coordination mechanisms established at the national level, and document best practices and lessons learned. Method We did a retrospective policy tracing of the COVID-19 coordination mechanisms from March 2020 (when first cases of COVID-19 in the AFRO region were reported) to the end of the third wave in September 2021. Data sources were from document and Literature review of COVID-19 response strategies, plans, regulations, press releases, government websites, grey and peer-reviewed literature. The data was extracted to Excel file database and coded then analysed using Stata (version 15). Analysis was done through descriptive statistical analysis (using measures of central tendencies (mean, SD, and median) and measures of central dispersion (range)), multiple linear regression, and thematic analysis of qualitative data. Results There are three distinct layered coordination mechanisms (strategic, operational, and tactical) that were either implemented singularly or in tandem with another coordination mechanism. 87.23% (n = 41) of the countries initiated strategic coordination, and 59.57% (n = 28) initiated some form of operational coordination. Some of countries (n = 26,55.32%) provided operational coordination using functional Public Health Emergency Operation Centres (PHEOCs) which were activated for the response. 31.91% (n = 15) of the countries initiated some form of tactical coordination which involved the decentralisation of the operations at the local/grassroot level/district/ county levels. Decentralisation strategies played a key role in coordination, as was the innovative strategies by the countries; some coordination mechanisms built on already existing coordination systems and the heads of states were effective in the success of the coordination process. Financing posed challenge to majority of the countries in initiating coordination. Conclusion Coordinating an emergency is a multidimensional process that includes having decision-makers and institutional agents define and prioritise policies and norms that contain the spread of the disease, regulate activities and behaviour and citizens, and respond to personnel who coordinate prevention.